Integrated Infiltration Runoff Drainage Assessment for Urban Pluvial Flooding at a Campus Scale in a Tropical Environment - Rabinah, Aiun Hayatu; Suparman, Suparman; Mahbub, Jamal; Parhadi, Parhadi; Larassati, Dian Sukma; Sulistiawati, Baiq Heny; Kusdiyanto, Rizky Aji (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2026)
Urban pluvial flooding frequently occurs in semi-urban tropical environments where intense rainfall exceeds local infiltration and drainage capacity. This study presents an integrated infiltration runoff drainage assessment at the campus scale to evaluate surface water inundation risk at Politeknik Negeri Semarang, Indonesia. Soil physical and hydraulic properties were characterized through laboratory testing, and infiltration behavior was simulated using the physically based Green–Ampt model under 2, 5, 10, and 20-year return period rainfall. Runoff was estimated using the Rational Method based on rainfall intensity corresponding to the time of concentration, while drainage storage capacity was quantified through field-based geometric measurements. The results indicate that the site is dominated by fine-grained soils (OH/MH; A-7-5) with very low saturated hydraulic conductivity (4.209 × 10⁻⁶ mm/s), limiting infiltration effectiveness to the early stage of rainfall. Infiltration rates rapidly decline toward saturated conductivity values, causing increasing rainfall increments to be converted directly into surface runoff. Estimated runoff volumes increase from 341.308 m³ (2-year) to 527.498 m³ (20-year return period). Although total drainage storage capacity (1270.38 m³) exceeds runoff volume, the storage margin decreases significantly under higher return periods, indicating increasing susceptibility to drainage surcharge. The integrated framework provides a process-based explanation of pluvial flooding driven by limited infiltration and drainage capacity utilization in tropical campus environments.